Decentralized Matching with Transfers: Experimental and Noncooperative Analyses - He, Simin; Wu, Jiabin; Zhang, Hanzhe; Zhu, Xun (American Economic Journal: Microeconomics, 2024)
We experimentally examine the Becker-Shapley-Shubik two-sided matching model. In the experiment, the aggregate outcomes of matching and surplus are affected by whether equal split is in the core and whether efficient matching is assortative; the canonical cooperative theory predicts no effect. In markets with an equal number of participants on both sides, individual payoffs cannot be explained by existing refinements of the core, but are consistent with our noncooperative model's predictions. In markets with unequal numbers of participants, noncompetitive outcomes, are not captured by the canonical cooperative model, but are included in the set of predictions in our noncooperative model.
Keywords: Bargaining Theory; Matching Theory; Noncooperative Games; Cooperative Games